2010
DOI: 10.1007/s10741-009-9157-7
|View full text |Cite
|
Sign up to set email alerts
|

Role and benefits of exercise in the management of patients with heart failure

Abstract: Initial research established the feasibility of exercise training in patients with heart failure, as well as associated physiological benefits. This review summarizes the findings from over two dozen single-site studies that address the effect of exercise training on exercise capacity and cardiovascular and peripheral function. In addition, it incorporates the results from two meta-analyses and a recently completed multi-center trial, all of which studied the effects of exercise training on clinical outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…One tested strategy is exercise/endurance training. In HF patients, exercise training seemed safe, increased mitochondrial inner surface membrane, improved exercise capacity, helped to attenuate abnormal HF pathophysiology and yielded a modest reduction in clinical events 7 . However, the use of exercise as a means to improve mitochondria structure can be problematic in patients with physical limitations thus, the need to identify alternate and safe strategies that trigger such effects.…”
Section: Discussionmentioning
confidence: 99%
“…One tested strategy is exercise/endurance training. In HF patients, exercise training seemed safe, increased mitochondrial inner surface membrane, improved exercise capacity, helped to attenuate abnormal HF pathophysiology and yielded a modest reduction in clinical events 7 . However, the use of exercise as a means to improve mitochondria structure can be problematic in patients with physical limitations thus, the need to identify alternate and safe strategies that trigger such effects.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reasons for the lack of improvement in endothelium-independent vasodilation may be inadequate delivery of blood to exercising skeletal muscle and reduced muscle sensitivity to nitric oxide [26]. The first point has been widely addressed in the literature [4,25]. Regarding the latter, investigators have suggested that the response of vascular smooth muscle in individuals who regularly take nitrate-based medications may attenuate to NO-mediated and cyclic guanosine monophosphate (cGMP) stimuli [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate use may need to be a consideration when using endothelium-independent vasodilation as an outcome variable. Finally, it is thought that the loss of endothelium-dependent vasodilation occurs early in the development of cardiovascular disease, but it is not clear if and when endothelium-independent vasodilation is reduced [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Endurance exercise training represents an effective way to provide relatively safe, non‐pharmacological therapy for mitigating subclasses of cardiac diseases (Keteyian et al . , ; Belardinelli et al . ), including lethal ventricular arrhythmias (Billman, ).…”
Section: Structural and Functional Organization Of The Cardiac Nervoumentioning
confidence: 99%